The Choice to Stick or Twist for Shareholders: A Review into UK Say-on-Pay - Millard, Ryan James (2013)
Say-on-Pay became a landmark in the development of executive remuneration, particularly in the UK, as it instigated the first regulated approach. This has provided an unrivalled foundation for studies and discussion. Although research has remarked on findings and begun to analyse its effectiveness, this still remains in a fragmented and conservative state. This review collates an array of theoretical, empirical and policy understandings to provide a clearer and more meaningful perspective. Say-on-Pay established amid weak remuneration policies, in an effort to reform the pay setting process. In theory the vote has significant tools to implement change in remuneration and governance. Whilst progress has been identifiable, uncertainty still remains over its value. The future is one of both exploration and change, exemplified by ever pertinent themes and a new binding vote, soon to create a new era. An overview of research into these matters enables an overall understanding and reflection on UK Say-on-Pay.